Evaluating the Impact of Language Concordance on Coronavirus Disease 2019 Contact Tracing Outcomes Among Spanish-Speaking Adults in San Francisco Between June and November 2020. (23rd December 2021) - Eliaz, Amity; Blair, Alden H; Chen, Yea-Hung; Fernandez, Alicia; Ernst, Alexandra; Mirjahangir, Joy; Celentano, Jessica; Sachdev, Darpun; Enanoria, Wayne; Reid, Michael J A
Abstract: We evaluated the impact of language concordance—clinician or public health worker fluency in a patient's primary language—on coronavirus disease 2019 (COVID-19) contact tracing outcomes among 2668 Spanish-speaking adults in San Francisco. Language concordance was associated with 20% greater odds of COVID-19 testing and 53% greater odds of support service referrals.